1987
DOI: 10.1080/00103628709367878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dip and vacuum infiltrations of various inorganic chemicals on post‐harvest quality of apple.

Abstract: Influence of dip, low, medium, and high vacuum applications of 5 inorganic chemicals on "Golden Delicious" apple was studied after 5 months of 0° C storage. Urea delayed ground color development, increased internal breakdown, but decreased firmness. Magnesium chloride induced severe incidence of a bitter pit-like symptom which did not have corky tissue. Soluble solids and titratable acidity were not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Role of Calcium: DeLong [6], Smock [17], and Garman and Mathis [18] were among the first researchers who found that bitter pit results from fruit Ca deficiency. Fruit Ca and ratios of other nutrients to Ca, are possibly the most important fac-tors affecting bitter pit formation in apples [4,[11][12][13][19][20][21][22][23][24][25][26][27]. Smock and Van Doren [28] described the first sign of bitter pit and reported that the cell walls of affected fruit collapses and plasmolysis occurs.…”
Section: Mineral Nutrients In the Fruitmentioning
confidence: 99%
See 2 more Smart Citations
“…Role of Calcium: DeLong [6], Smock [17], and Garman and Mathis [18] were among the first researchers who found that bitter pit results from fruit Ca deficiency. Fruit Ca and ratios of other nutrients to Ca, are possibly the most important fac-tors affecting bitter pit formation in apples [4,[11][12][13][19][20][21][22][23][24][25][26][27]. Smock and Van Doren [28] described the first sign of bitter pit and reported that the cell walls of affected fruit collapses and plasmolysis occurs.…”
Section: Mineral Nutrients In the Fruitmentioning
confidence: 99%
“…High fruit K and Mg are also believed to increase bitter pit incidence regardless of Ca content [47]. Fallahi, et al [21] were able to induce severe bitter pit symptoms in 'Golden Delicious' apple fruit by vacuum infiltration of Mg, and thus increasing Mg/Ca ratio in the fruit tissue. Baugher, et al [48] reported a strong correlation between fruit N/Ca ratio and bitter pit.…”
Section: Mineral Nutrients In the Fruitmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of balanced nutrition on apple fruit storability and quality has been well documented (Dris and Niskanen, 1999;Lanauskas and Kvikliene, 2006). Among the nutrients calcium is the most important affecting quality of apple and pear fruits (Fallahi et al, 1987). Calcium affects fruit senescence and quality by altering intracellular and extracellular processes and the rate of fruit softening depending on the fruit Ca status.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure infiltration Sams 1983, 1987;Drake and Fridlund 1986;Sams and Conway 1984) and vacuum infiltration (Conway and Sams 1983;Fallahi et al 1986) of calcium salt solutions into apples have significantly elevated flesh calcium content ofthe fruit. Also effective have been dips in solutions containing a calcium salt and a thickener (Mason 1979 but not in 1984 (Tables 2 and 3) for Drake andFridlund (1986), Sams andConway (1984) and Conway and Sams (1987) agree with those in our study ( …”
mentioning
confidence: 99%